Chemical Composition and Larvicidal Activity of the EssentialOil of Laurus nobilisL. from Iran: Essential oil of Laurus nobilis - Mohammadreza Verdian-Rizi, (Iranian Journal of Pharmaceutical Sciences, 2009)
The chemical composition of the essential oil obtained from the aerial parts of Laurus nobilisL. has been examined by gas chromatography (GC) and GC- mass spectrometery (MS). The main components of the oil were identified. 1,8-Cineole was the major component in the oil together with ß-terpinyl acetate, terpinene-4-ol, α-pinene, ß-pinene, p-cymene, linalool and terpinene-4-ylacetate. The essential oil was tested against Anopheles stephensi and Culex pipienslarvae. The results obtained show that the essential oil could be considered as natural larvicidal agents.